PERAN ORGANISASI REMAJA MASJID DALAM KEGIATAN KEAGAMAAN, SOSIAL DAN EKONOMI PADA ORGANISASI MASJID DAARUL FALAAH PAMULANG TIMUR, KOTA TANGERANG SELATAN - Dede Hendra; Rr Renny Anggraini; Amirudin Amirudin; Ida Nurlina; Budi Haryono (Universiitas Pamulang, 2022)
ABSTRACT The purpose of carrying out Community Service (PKM) activities is to help the youth organization of the Daarul Falaah mosque to be able to maximize the function of the mosque, where the mosque is not just for worship activities, but there are many activities that can be done from the mosque, namely social and economic activities. Social activities can be carried out in mosques such as charity events for orphans, counseling activities and other activities. Economic activities can also be carried out in mosques, mosques in this era are broader in function so that these economic activities can be carried out from mosques. Many mosques have performed this function so that the mosque can be independent and provide broad benefits for the surrounding community or for the ummah in general. All of the above activities can be carried out if managed properly, and one of the mosque managers is the mosque organization itself such as the mosque youth organization or often called IRMAS (Ikatan Pemuda Masjid). In addition, with this activity, the function of the Daarul Falaah Mosque Youth Organization can carry out its role optimally.. Keywords: Mosque Youth Organization, Religion, Social and Economic ABSTRAK Tujuan dilaksanakannya kegiatan Pengabdian Kepada Masyarakat (PKM) adalah untuk membantu organisasi remaja masjid Daarul Falaah agar bisa bisa memaksimalkan fungsi masjid, dimana masajid bukan hanya sekedar untuk kegiatan ibadah semata melainkan banyak kegiatan yang bisa dilakukan dari masjid yaitu kegiatan sosial dan ekonomi. Kegiatan sosial bisa dilakukan di masjid seperti acara santunan anak yatim, kegiatan penyuluhan dan kegiatan lainnya. Kegiatan ekonomi juga bisa dilakukan di masjid, masjid di era sekang lebih luas fungsinya sehingga kegiatan ekonomi ini bisa dilakukan dari masjid. Banyak masjid yang sudah melakukan fungsi ini sehingga masjid tersebut bisa mandiri dan memberikan manfaat yang luas untuk masyarakat sekitar atau untuk ummat secara umumnya. Semua kegiatan diatas bisa terlaksana apabila dikelola dengan baik, dan salah satu pengelola masjid adalah organisasi masjid itu sendiri seperti organisasi remaja masjid atau sering disebut IRMAS (Ikatan Remaja Masjid). Disamping itu, dengan adanya kegiatan ini fungsi Organisasi Remaja Masjid Daarul Falaah ini bisa secara maksimal menjalankan perannya.Kata Kunci: Organisasi Remaja Masjid, Keagamaan, Sosial dan Ekonomi